Adipose microenvironment promotes hypersialylation of ovarian cancer cells - Fox, Alexandra; Leonard, Garry D.; Adzibolosu, Nicholas; Wong, Terrence; Tedja, Roslyn; Sharma, Sapna; Gogoi, Radhika; Morris, Robert; Mor, Gil; Fehl, Charlie; Alvero, Ayesha B. (Frontiers in Oncology, 2024)
Introduction Ovarian and other peritoneal cancers have a strong tendency to metastasize into the surrounding adipose tissue. This study describes an effect of the adipose microenvironment on upregulation of sialic acid-containing glycans in ovarian cancer (OC). Heterogeneous populations of glycosylated OC tumors converged to a highly sialylated cell state that regulates tumorigenesis in an immune-dependent manner. Methods We modeled the adipose microenvironment by conditioning growth media with human patient-derived adipose tissue. OC cell lines grown in the presence vs. absence of adipose conditioned media (ACM) were characterized by transcriptomics, western blotting, and chemical biology glycan labeling methods. Fluorescence-activated cell sorting was used to separate adipose-driven upregulation of hypersialylated (“SNA-high”) vs. hyposialylated (“SNA-low”) OC subpopulations. The two subpopulations were characterized by further transcriptomic and quantitative polymerase chain reaction analyses, then injected into a syngeneic mouse model. Immune system involvement was implicated using wild type and athymic nude mice with a primary endpoint of overall survival. Results Adipose conditioning resulted in upregulation of sialyltransferases ST3GAL1, ST6GAL1, ST6GALNAC3, and ST8Sia1. In culture, OC cells displayed two distinct sialylated subpopulations that were stable for up to 9 passages, suggesting inherent heterogeneity in sialylation that is maintained throughout cell division and media changes. OC tumors that implanted in the omental adipose tissue exclusively reprogrammed to the highly sialylated subpopulation. In wild type C57BL/6 mice, only the hypersialylated SNA-high subpopulation implanted in the adipose, whereas the hyposialylated SNA-low subpopulation failed to be tumorigenic (p=0.023, n=5). In the single case where SNA-low established a tumor, post-mortem analysis revealed reprogramming of the tumor to the SNA-high state in vivo. In athymic nude mice, both subpopulations rapidly formed tumors, implicating a role of the adaptive immune system. Conclusions These findings suggest a model of glycan-dependent tumor evolution wherein the adipose microenvironment reprograms OC to a tumorigenic state that resists the adaptive immune system. Mechanistically, adipose factors upregulate sialyltransferases. To our knowledge, this is the first demonstration of the effect of adipose microenvironment on OC tumor sialylation. Our results set the stage for translational applications targeting sialic acid pathways in OC and other peritoneal cancer tumorigenesis and metastasis.